Carbapenemase-Producing Extraintestinal Pathogenic Escherichia coli From Argentina: Clonal Diversity and Predominance of Hyperepidemic Clones CC10 and CC131 - Sanz, María Belén; De Belder, Denise; de Mendieta, JM; Faccone, Diego; Poklepovich, Tomás; Lucero, Celeste; Rapoport, Melina; Campos, Josefina; Tuduri, Ezequiel; Saavedra, Mathew O.; Van der Ploeg, Claudia; Rogé, Ariel; et al. (Frontiers in Microbiology, 2022)
Extraintestinal pathogenic Escherichia coli (ExPEC) cause infections outside the intestine. Particular ExPEC clones, such as clonal clomplex (CC) CC//sequence type (ST)131, have been known to sequentially accumulate antimicrobial resistance that started with chromosomal mutations against fluoroquinolones and followed with the acquisition blaCTX-M-15 and more recently carbapenemases. Here, we aimed to investigate the distribution of global epidemic clones of carbapenemase-producing ExPEC from Argentina in representative clinical isolates recovered between July 2008 and March 2017. Carbapenemase-producing ExPEC (n=160) were referred to the Argentinean reference laboratory. Of these, 71 were selected for genome sequencing. Phenotypic and microbiological studies confirmed the presence of a carbapenemases confirmed as KPC-2 (n=52), NDM-1 (n=16), IMP-8 (n=2) and VIM-1 (n=1) producers. The isolates had been recovered mainly from urine, blood, abdominal fluids, etcamong others. and some from screening samples. After analyzing virulence gene content, 76% of the isolates were considered ExPEC, although non-ExPEC isolates were also obtained from extraintestinal sites. Pan-genome phylogeny and clonal analysis showed great clonal diversity although the first phylogroup in abundance was phylogroup A, harboring CC10 isolates, followed by phylogroup B2 with CC/ST131, mostly H30Rx, the subclone co-producing CTX-M-15. Phylogroup D, B1, C, F and E were also detected with fewer strains. CC10 and CC/ST131 were found throughout the country. In addition, CC10 nucleated most metalloenzymes such as NDM-1. Other relevant international clones were identified such as CC/ST38, CC155, CC14/ST1193 and CC23. Two isolates co-produced KPC-2 and OXA-163 or OXA-439, a point mutation variant of OXA-163, and three isolates co-produced MCR-1, among other resistance genes. To conclude, in this work we described the molecular epidemiology of carbapenemase-producing ExPEC in Argentina. Further studies are necessary to determine the plasmid families disseminating carbapenemases in ExPEC in this region.